EFEK PELAYANAN SENYUM, SALAM, SAPA PETUGAS KASIR TERHADAP KEPUASAN KONSUMEN SUPERMARKET - Febrianto, Muhammad Riza; Widiana, Herlina Siwi (Faculty of Psychology, Diponegoro University, 2013)
This research was experimental research aimed at knowing the effect of smiling, greeting, and addressing of cashier toward the satisfaction of supermarket’s customers. This research used posttest only control group design. The subject were 62 customers of supermarket X.4. They were randomly divided into two groups, experiment group and control group. The Mann-Whitney U Test was used to analyze the costumer statisfaction. The result show there is significant difference between experimental group and control group after receive service with smiling, greeting and addressing from cashier. The research result show that smiling, greeting and addressing of cashier influences the satisfaction of supermarket’s customers effectively.